2016
DOI: 10.5152/tjbh.2016.3070
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Affect Drain Indwelling Time after Breast Cancer Surgery

Abstract: Objective:The most common procedure to prevent seroma formation, a common complication after breast and axillary surgery, is to use prophylactic surgical drains. Ongoing discussions continue regarding the ideal time for removing drains after surgical procedures. In this study, we aimed to investigate factors that affect drain indwelling time (DIT). Materials and Methods: From 2014 to 2015, a total of 91 consecutive patients with breast cancer were included in the study. The demographic characteristics of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Uslukaya et al reported that there was a positive correlation between the histopathologic features of the tumor, size of removed breast tissue (BS), tumor size (TS), number of totally removed lymph nodes (TLN) and metastatic lymph nodes (MLN) and the drain indwelling time (DIT). 19 Similarily, Eldesouky et al found that the mean duration of drainage was also lower in the study group as compared with the control group (9.85±1.66 versus 11.67±1.9 days; p<0.005); this difference was significant. 9 However, in Barwell et al study, suction drains were removed at the ward after a median of 4 days (range 1-7 days) for wide local excision of breast carcinoma and the median of suction drain removing for mastectomy with axillary dissection was about 12 days (range 10-14 days).…”
Section: Discussionsupporting
confidence: 67%
“…Uslukaya et al reported that there was a positive correlation between the histopathologic features of the tumor, size of removed breast tissue (BS), tumor size (TS), number of totally removed lymph nodes (TLN) and metastatic lymph nodes (MLN) and the drain indwelling time (DIT). 19 Similarily, Eldesouky et al found that the mean duration of drainage was also lower in the study group as compared with the control group (9.85±1.66 versus 11.67±1.9 days; p<0.005); this difference was significant. 9 However, in Barwell et al study, suction drains were removed at the ward after a median of 4 days (range 1-7 days) for wide local excision of breast carcinoma and the median of suction drain removing for mastectomy with axillary dissection was about 12 days (range 10-14 days).…”
Section: Discussionsupporting
confidence: 67%
“…Our study demonstrated that neoadjuvant chemotherapy significantly increased the mean duration of surgery and the mean duration of the drain placement. These findings are in concordance with studies conducted by Gümüş et al 17 and Uslukaya et al 18 Both these studies reported increased mean duration of surgery and mean duration of drain in patients who underwent neoadjuvant chemotherapy. They also reported increased length of hospital stay with neoadjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…Of the articles included, three were randomized controlled trials, one was a nonrandomized controlled trial, and three were retrospective chart reviews representing a total of 1226 patients (TXA, 632 patients; control, 622 patients) (Table 1). 1–60 ( See Table, Supplemental Digital Content 6 , which shows demographic information, http://links.lww.com/PRS/G260. )…”
Section: Resultsmentioning
confidence: 99%